English Learning in Islamic Boarding School Al-Junaidiyah Biru Bone (Ethnographic Studies) - Suardi Suardi; Emzir Emzir; Zainal Rafli (STKIP Singkawang, 2017)
This study aims to analyze the process of learning English in Islamic boarding school Al-Junaidiyah Biru Bone. Using ethnographic methods. The results of the study show that (1) analyzing the needs and the environmental context in the formulation of learning objectives, (2) using 2 curriculum that is the curriculum of 2013 for general subjects and the curriculum of special pesantren religious subjects, (3) adjustment of learning materials with context, social function , text structure, and linguistic elements, (4) using approach (Contextual Teaching and Learning-CTL), (5) Educators, and learners have a mutually exciting learning role to be interesting and fun, (6) developed language environments such as the implementation of English flag ceremonies, sports competitions and the arts that use English in extracurricular activities. The conclusion of the effort to habituate the use of English and has four language skills, namely listening, speaking, reading and writing.